2014
DOI: 10.1038/ni.2918
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative and temporal requirements revealed for Zap70 catalytic activity during T cell development

Abstract: The catalytic activity of Zap-70 is crucial for T cell receptor (TCR) signaling, but the quantitative and temporal requirements for its function in thymocyte development are not known. Using a chemical-genetic system to selectively and reversibly inhibit Zap-70 catalytic activity in a model of synchronized thymic selection, we showed that CD4+CD8+ thymocytes integrate multiple, transient, Zap-70-dependent signals over more than 36 h to reach a cumulative threshold for positive selection, whereas one hour of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
96
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 37 publications
10
96
0
Order By: Relevance
“…1E). These data extend and confirm our analysis of the temporal requirement for TCR signaling (21) and indicate that TCR signaling is required at both early and late time points for efficient positive selection.…”
Section: Resultssupporting
confidence: 86%
“…1E). These data extend and confirm our analysis of the temporal requirement for TCR signaling (21) and indicate that TCR signaling is required at both early and late time points for efficient positive selection.…”
Section: Resultssupporting
confidence: 86%
“…This model is consistent with recent studies in which we demonstrate the existence of a temporal threshold for positive selection of CD4 + CD8 + double positive thymocytes, which correlates with an integration of multiple transient encounters with positively selecting ligands. We further show that interruptions in Zap70-dependent signaling decreased the frequency and duration of these signaling events, impairing the efficiency of positive selection (33).…”
Section: Discussionmentioning
confidence: 65%
“…Zap70(AS) inhibitor HXJ42 has been described previously (33). CD4, CD8, CD25, CD90.2, and CD45.1 antibodies conjugated to PE, PerCPCy5.5, PECy7, APC, or Qdot 605 (BD Biosciences, eBioscences, Life Technologies), Nur77 Ab conjugated to PE (eBiosciences; clone 12.14).…”
Section: Zap70mentioning
confidence: 99%
“…Additionally, a reporter mouse model in which GFP levels reflect TCR signal strength revealed that nTregs show higher levels of sustained TCR signaling than do Tconvs in the thymus (19). The observations that different temporal TCR signaling patterns, namely sustained and transient signals, are associated with positive and negative selections (40)(41)(42)(43)(44)(45)(46)(47) underpin the relevance of the dynamics of TCR stimulation for thymocyte selection. Therefore, the history of TCR stimulation has to be taken into account for a model of thymic selection.…”
mentioning
confidence: 97%
“…The disruption of thymocyte-APC interactions or blockade of TCR signaling at different selection stages prevents successful positive selection, implying a requirement for sustained signals (38)(39)(40). In contrast to positive selection, negative selection is a fast process and requires a strong TCR signaling event (41). Negative selection is preceded by a strong transient increase of TCR-mediated signals (42).…”
mentioning
confidence: 99%